2014
DOI: 10.1186/s12966-014-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomised feasibility trial of a teaching assistant led extracurricular physical activity intervention for 9 to 11 year olds: Action 3:30

Abstract: BackgroundExtracurricular programmes could provide a mechanism to increase the physical activity (PA) of primary-school-aged children. The aim of this feasibility study was to examine whether the Action 3:30 intervention, which is delivered by teaching assistants, holds promise as a means of increasing the PA of Year 5 and 6 children.MethodsA cluster randomised feasibility trial was conducted in 20 primary schools. Ten schools received the Action 3:30 intervention and 10 schools were allocated to the control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(89 citation statements)
references
References 37 publications
5
82
2
Order By: Relevance
“…Discovering a department's weaknesses in terms of TA teaching styles also would prove beneficial in identifying not only what the instructor can improve on, but also what a department should train their TAs to teach. TAs do not feel adequately trained, and the results of this study suggest the same, but specifically to classroom management [1]. Future research could explore this idea more in-depth by measuring teaching effectiveness of TAs who are taking a course in classroom management as opposed to a control group who receives only basic training to be a TA.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Discovering a department's weaknesses in terms of TA teaching styles also would prove beneficial in identifying not only what the instructor can improve on, but also what a department should train their TAs to teach. TAs do not feel adequately trained, and the results of this study suggest the same, but specifically to classroom management [1]. Future research could explore this idea more in-depth by measuring teaching effectiveness of TAs who are taking a course in classroom management as opposed to a control group who receives only basic training to be a TA.…”
Section: Discussionmentioning
confidence: 90%
“…Over time, teaching assistants have taken a greater role in teaching and managing students, as evidenced by teaching assistants leading an after school program [1]. Teaching assistants are serving a greater role in the classroom by frequently being listed as the instructor of record for many physical education classes [2].…”
mentioning
confidence: 99%
“…38 The Action 3 : 30 trial trained teaching assistants to deliver after-school PA sessions to 9-to 11-year-old children; weekday MVPA for boys increased by 8.6 minutes per day (95% CI 2.8 minutes to 14.5 minutes). 39 Both Madsen et al 42 and Dzewaltowski et al 40 found a significant increase in MVPA in an overweight subsample of children. The SCORES programme used soccer to support the development of skills and competencies among 9-and 10-year-old students and resulted in an increase in MVPA of 3.4 minutes per weekday (95% CI 0.3 minutes per weekday to 6.5 minutes per weekday; p-value not reported) among students with a body mass index (BMI) at or above the 85th percentile.…”
Section: After-school Interventionsmentioning
confidence: 93%
“…[32][33][34]36,37 A recent literature search revealed that since these reviews, there have been five randomised controlled trials [38][39][40][41][42] that employed objective measures of PA in evaluating the effectiveness of a school-based intervention to increase PA levels. Of these, two were feasibility trials 38,39 and one was a cross-sectional study. 40 Looking at the five studies, withdrawal and drop-out rates were low (< 20%); however, attendance varied widely, thus compromising intervention integrity.…”
Section: After-school Interventionsmentioning
confidence: 99%
See 1 more Smart Citation